PENERAPAN PEMBELAJARAN TEAMS GAMES TOURNAMENT DALAM MENINGKATKAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS XA SMK NURUL IMAN MUNTILAN - Fitri Yuliani (Universitas Sarjanawiyata Tamansiswa, 2015)
This study aims to determine how the approach TGT cooperative learning model in order to improve student achievement in math class XA SMK Nurul Iman Muntilan. The study took place in two cycles with research subjects were students of class XA SMK Nurul Iman Muntilan Magelang Regency school year 2011/2012, amounting to 31 students. Objects in this research is the implementation of the process and the results obtained from the application of mathematics learning with cooperative learning model approach TGT in class XA SMK Nurul Iman Muntilan Magelang regency school year 2011/2012 as many as 31 students. Data collection techniques in this study with the observation, testing, documentation record and field notes. Test instrument used was a test pilot. Data analysis techniques for motivation observation done by calculating the percentage of each indicator. Test instrument used was a test pilot. As for the achievement test is done by calculating the average value and the percentage of students who meet the KKM. Results showed an increase student achievement in the learning process for each cycle compare withÂ test value in pre-cycle. Average value in pre-cycle 62,5 increased in the first cycle to 68,2 and the second cycle increased to 75,1. Percentage of students who meet the KKM also increased in pre-cycle 25,81% fixed with 48,39% in the first cycle, and the second cycle increased to 83,87%. The results could be a mathematics teacher input to increase mathematics achievement through cooperative Teams Games Tournament (TGT).